Does foreign investment liberalisation enhance women's economic status? Micro‐evidence from urban China. (3rd November 2019) - Yu, Linhui; Zhang, Junsen; Wen, Yanbing
Abstract: This paper analyses the effects of inward foreign direct investment (FDI) on female earnings and women's economic status in households using Chinese Urban Household Survey data from 1997 to 2008. The identification exploits the substantial relaxation of foreign investment regulations immediately after China's accession to the WTO in 2002. The difference‐in‐differences estimation results show that FDI liberalisation has improved women's economic status significantly by increasing female earnings in sectors more exposed to FDI. Further analyses indicate that foreign investment liberalisation facilitates the promotion of female employees in their career ladders and increases their skill premium, which are two important channels through which women enhance their economic independence.